Ethnomedicine Study of Medicinal Plants in the Menoreh Salaman Village Community as a Biology Reference Book - Fiki Wafara Amali; Setiyo Prajoko; Shefa Dwijayanti Ramadanti (BIOEDUKASI, 2023)
Utilization of biodiversity, especially plants as ingredients for traditional medicine is a tradition of rural communities in Indonesia. Villagers know traditional medicine from their ancestors which has been passed down from generation to generation. However, knowledge regarding the use of plants for traditional medicine has not been well documented, proving that this knowledge is only mastered by the elderly. Ethnomedicine study is one solution that can be done to overcome this problem. The diversity of plants used by the community for treatment has the potential as a biological reference source. This study aims to identify plants used for traditional medicine by the people of Menoreh Village and to develop and produce a product in the form of a reference book based on the results of the ethnomedicine study conducted. This study uses ethnographic study methods and 4D Research and Development (R&D) models but only up to the develop stage. Collecting data using the method of observation, interviews, and questionnaires. Data analysis techniques using qualitative and quantitative descriptive analysis. The results showed that there were 79 species of plants belonging to 27 orders. The plants most often used are kencur and awar-awar. The most widely used part of the plant is the leaf, the most common processing method is boiling, the dominant way of use is drinking and the disease that is most commonly treated with medicinal plants, namely coughs and colds. good and worth using with revision. The feasibility assessment of reference books by media experts is 74.6% with sufficient eligibility criteria and is suitable for use with revisions. The overall feasibility of reference books obtained an average value of 82.46% with good criteria.